2018
DOI: 10.1155/2018/6757368
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 Deficiency Induces Autophagy Dysfunction via Lysosomal Impairment and Amplifies Sepsis-Induced Acute Lung Injury

Abstract: Sepsis is a systemic inflammatory reaction caused by infection. Multiple organ failure ultimately leads to high morbidity and mortality. Unfortunately, therapies against these responses have been unsuccessful due to the insufficient underlying pathophysiological evidence. Protein interacting with C-kinase 1 (PICK1) has received considerable attention because of its important physiological functions in many tissues. However, its role in sepsis-induced acute lung injury (ALI) is unclear. In this study, we used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…ALI has been found to be associated with inflammatory responses, neutrophil infiltration, oxidative stress and the accumulation of pro-tein-rich fluid in the lung (Kissoon et al, 2016). As previously reported, patients with sepsis-induced ALI have a poor outcome, with mortality rates of more than 40% (Mo et al, 2018). Currently available treatments for ALI, antibiotics and pulmonary supportive measures, can hardly improve the outcome of the patients (Aziz et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…ALI has been found to be associated with inflammatory responses, neutrophil infiltration, oxidative stress and the accumulation of pro-tein-rich fluid in the lung (Kissoon et al, 2016). As previously reported, patients with sepsis-induced ALI have a poor outcome, with mortality rates of more than 40% (Mo et al, 2018). Currently available treatments for ALI, antibiotics and pulmonary supportive measures, can hardly improve the outcome of the patients (Aziz et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…In vivo experiments also found that PICK1 deficiency caused a disruption of autophagy progress and amplified the damage in sepsis-induced ALIs. Lysosomal damage caused by PICK1 deficiency may be responsible for the impediment of autophagy flux (Mo et al, 2018). Another experiment found that the AMPK activator might improve lung recovery through the activation of mitochondrial biogenesis via the increased expression of PGC-1α.…”
Section: Mechanism Of Action Of Autophagy In Different Organsmentioning
confidence: 99%
“…Studies have proved that cytokine bursts caused by uncontrolled inflammatory responses could induce severe damage in tissue and organ, even causing death [17]. Acute organ dysfunction is a common respiratory and cardiovascular complication of sepsis [18]. The lung is the easiest infection target in sepsis, which also plays a critical role in the secretion and release of inflammatory mediators [19].…”
Section: Discussionmentioning
confidence: 99%